2004
DOI: 10.1038/sj.onc.1207953
|View full text |Cite
|
Sign up to set email alerts
|

Deacetylation of p53 after nerve growth factor treatment in PC12 cells as a post-translational modification mechanism of neurotrophin-induced tumor suppressor activation

Abstract: The tumor suppressor protein p53 is a transcription factor that regulates the response to cellular insults such as DNA damage and growth factor withdrawal. Transcriptional activity of p53 requires post-translational modification by phosphorylation and acetylation. This study used sitespecific antibodies to demonstrate that nerve growth factor (NGF) treatment of PC12 cells results in p53 deacetylation at lysine (Lys) 382. Histone deacetylase (HDAC) activity, measured by a direct fluorescent assay, was increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 80 publications
0
18
0
Order By: Relevance
“…Vaghefi et al (38) revealed that deacetylation of p53 was a nerve growth factor (NGF)-dependent post-translational mechanism of p53 activation. Additionally, Richardson et al (39) reported that NGF had increased expression in the painful degenerate intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…Vaghefi et al (38) revealed that deacetylation of p53 was a nerve growth factor (NGF)-dependent post-translational mechanism of p53 activation. Additionally, Richardson et al (39) reported that NGF had increased expression in the painful degenerate intervertebral disc.…”
Section: Discussionmentioning
confidence: 99%
“…Parc interacts with and sequesters p53 in the cytoplasm and, therefore, prevents its translocation to the nucleus (46). Histone deacetylase 1 (HDAC-1) down-regulates p53-dependent gene activation by reducing the acetylation level of p53, whereas nerve growth factor promotes the p53 deacetylation by increasing HDAC-1 activity (47,48). SV 40 large antigen and Plk1 interact with the DNA binding domain and attenuate the binding of p53 to promoter, thus repressing p53 transcriptional activity (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…The potential mechanisms whereby p53 levels increase in TrkA-expressing NB cells remain to be identified, and they include HDM2-induced ubiquitination or neddylation, or TAF-1-stimulated phosphorylation of p53 (53,54). In addition, TrkA may signal to p53 in other ways, because it can bind both p53 and c-Abl, a p53 activator (55)(56)(57), and promote the deacetylation of p53 in PC12 cells (58). It is likely that the modulation of p53 and Bcl-2 levels by TrkA occurs at the post-transcriptional level, because several recent cDNA expression profiling studies on NB tumors or SH-SY5Y NB cells stably transfected with TrkA did not report changes in p53 or Bcl-2 genes expression (59,60).…”
Section: Discussionmentioning
confidence: 99%